KITAB ‘AUN AL MA’BÛD ‘ALA SYARH SUNAN ABI DAUD - Hafizzullah Hafizzullah; Sefri Auliya (IAIN Batusangkar, 2018)
Sunan Abi Daud is one of the books of hadith mu'tabarah which is the main foundation for Muslims in referring to the traditions of the Prophet. But this book, like the other hadith books, requires an explanation so that the meaning and the law can be understood well. Many scholars have tried to deliberate and explain the laws of their traditions, starting from classical times to modern times, among them is the book of shari'a known as nama AUN AL MA'BÛD ‘ALA SYARH SUNAN ABI DAUD. In this study, the author applies the reseach library method by making the book ‘AUN AL MA'BÛD‘ ALA SYARH SUNAN ABI DAUD as the main book of research objects and supported by various other sources. The problem in this study is to reveal the identity of the author of this book, the background of the writing of this book, and the method used by the author in directing this book. From the research, it was found that the identity of the author of this book was two religious scholars from India who were motivated by Syams al-Haq's desire for his brother Syarf al-Haq to write a simple book of the Sunan Abi Daud which had no length. And the method used by Syarf al-Haq in counseling this book is the simple and simple method of shar tahlli